Prevalence of viruses in stool of premature neonates at a neonatal intensive care unit. Issue 3 (22nd February 2013) - Naing, Zin; Rayner, Benjamin; Killikulangara, Ananthen; Vunnam, Krishna; Leach, Steven; McIver, Christopher J; Scott, Gillian M; Craig, Maria E; Lui, Kei; Rawlinson, William D
<x xml:space="preserve">Abstract</x> Aim Premature neonates represent a population highly vulnerable to infection. This study aims to profile viral colonisation of gut and the associated clinical manifestations among premature neonates admitted to a neonatal intensive care unit (NICU) in Australia. Methods In a cohort of 75 premature neonates born at less than 32 weeks gestation, who were followed for 4 weeks following admission to a NICU in Sydney, Australia, multiplex polymerase chain reaction assays were used to determine viral presence in stool, and clinical data were examined. Results Overall, viral RNA or DNA was detected in 24/419 (5.7%) of specimens, including norovirus genogroup 2 (1.9%), enterovirus (1.2%), herpes simplex virus‐2 (1.2%), cytomegalovirus (0.7%), Epstein‐Barr virus (0.5%) and rotavirus (0.2%). Viral infection was detected in 13/75 (17%) of premature neonates at some time point, including five (7%) neonates shedding more than one type of virus in stool. A higher rate of infection was observed among premature neonates with intrauterine growth restriction (56%) compared with those infants born appropriate for gestational age (12%. P = 0.006). Conclusion The overall viral detection rate in stool of 5.7% (affecting 17% of neonates) indicates viral infections are an important health risk for premature infants in NICU.